ANALYSIS OF ASPERGER SYNDROME OF THE MAIN CHARACTER IN "MY NAME IS KHAN" MOVIE: A PSYCHOLINGUISTIC APPROACH - Yuspita, Eris (ReALL - Research on Applied Linguistics and Literature, 2024)
This research investigated the Asperger's Syndrome experienced by Khan in My Name Is Khan movie. Nathan is an Indian Muslim with Asperger's syndrome who goes to America to meet the president and his personal life with his wife, Mandhira. My Name is Khan made it into 29 nominations at various events. Of the 29 nominations, a total of 23 of them were won by the film directed by Karan Johar. Therefore, the researcher is interested in examining the language disorder in this film. This study aims to identify the characteristics of Asperger’s syndrome and types of language disorders that are shown in My Name is Khan movie. The data in this research were taken from My Name is Khan movie. In analyzing this movie, the theory formulated by Mesibov et al. (2001), Suherman (2016), and Chaer (2003) was used to analyze the characteristics of Asperger's Syndrome and the types of language disorders that Khan suffered. This research used the qualitative method. The finding shows that there are five sub-characteristics of Asperger's Syndrome that Nathan has; impairment in multiple nonverbal behaviors, difficulty in building a friendship, lack of social or emotional reciprocity, abnormal restricted patterns of readability either in intensity or focus and interest in a piece of some objects. In addition, Khan frequently experienced expressive language disorder (60%), followed by receptive language disorder (40%).